2013
DOI: 10.1371/journal.pone.0068208
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ectopic Migration of Granule Cells into the Hilus on Dentate Gyrus-CA3 Function

Abstract: Postnatal neurogenesis of granule cells (GCs) in the dentate gyrus (DG) produces GCs that normally migrate from the subgranular zone to the GC layer. However, GCs can mismigrate into the hilus, the opposite direction. Previous descriptions of these hilar ectopic GCs (hEGCs) suggest that they are rare unless there are severe seizures. However, it is not clear if severe seizures are required, and it also is unclear if severe seizures are responsible for the abnormalities of hEGCs, which include atypical dendrite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
83
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 113 publications
(210 reference statements)
8
83
0
1
Order By: Relevance
“…Our observations that limbickindled rats had significantly more BrdU-ir hilar-CA3 ectopic granule cells and DCX-ir neurons containing hilar basal dendrites paralleled significant memory impairments on the trace fear conditioning memory test. It was recently shown that the presence of a small population of hilar-CA3 ectopic granule cells can disrupt pattern separation and completion-processes that are critical for hippocampal-dependent spatial learning and memory [63]. Our behavioral results in combination with our postmortem analyses support this notion.…”
Section: Discussionsupporting
confidence: 84%
“…Our observations that limbickindled rats had significantly more BrdU-ir hilar-CA3 ectopic granule cells and DCX-ir neurons containing hilar basal dendrites paralleled significant memory impairments on the trace fear conditioning memory test. It was recently shown that the presence of a small population of hilar-CA3 ectopic granule cells can disrupt pattern separation and completion-processes that are critical for hippocampal-dependent spatial learning and memory [63]. Our behavioral results in combination with our postmortem analyses support this notion.…”
Section: Discussionsupporting
confidence: 84%
“…In the case of seizures, hilar ectopic granule cells have been demonstrated to contribute to a hyperexcitable recurrent hippocampal circuitry. 32,33 This circuit has also been demonstrated anatomically [15][16][17] and in previous studies using the same FPI model. It has been demonstrated that this model has anatomical alterations consistent with aberrant hippocampal circuitry.…”
Section: Discussionsupporting
confidence: 73%
“…Rodents are the focus here. In Figure 1, several elements of the fundamental circuitry are simplified or collapsed for implementation in a computational model of the DG and CA3 (Myers & Scharfman, 2011; Myers et al, 2013). In brief, the primary glutamatergic input from cortex is the perforant path, formed by axons of neurons of layer II of the entorhinal cortex.…”
Section: Introductionmentioning
confidence: 99%